2013
DOI: 10.1111/1365-2745.12142
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative or competitive effects of woody plants on understorey vegetation depend on N‐fixation, canopy shape and rainfall

Abstract: Summary 1.A recent meta-analysis suggested that differences in rainfall are a cause of variation in tree-grass interactions in savannas, with trees facilitating growth of understorey grasses in low-rainfall areas, but competing with them under higher rainfall. We hypothesized that this effect of rainfall upon understorey productivity is modified by differences in the growth form of the woody plants (i.e. the height of the lower canopy) or by their capacity to fix nitrogen. 2. We performed a meta-analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 26 publications
6
72
1
1
Order By: Relevance
“…We now turn to mechanisms that govern the ecological interactions between grasses and trees or shrubs. There is a large body of ecological and rangemanagement literature on the effects of woody plants on grasses (Scholes and Archer 1997;Blaser et al 2013;Dohn et al 2013). Here, we focus on factors that influence recruitment and abundance of woody plants into grass-dominated communities.…”
Section: Population Interactions Between Grasses and Woody Plantsmentioning
confidence: 99%
“…We now turn to mechanisms that govern the ecological interactions between grasses and trees or shrubs. There is a large body of ecological and rangemanagement literature on the effects of woody plants on grasses (Scholes and Archer 1997;Blaser et al 2013;Dohn et al 2013). Here, we focus on factors that influence recruitment and abundance of woody plants into grass-dominated communities.…”
Section: Population Interactions Between Grasses and Woody Plantsmentioning
confidence: 99%
“…Positive effects are mainly due to shelter and improved soil fertility, negative impacts due to competition for light, water and nutrients . Further studies are needed to understand under which ecological conditions and plants traits the tree effects change from net competitive to net facilitative (Blaser et al, 2013). The number of young trees to be encouraged in open ground or left after thinning in-filled wood-pasture must allow for mortality (Lonsdale, 2013): not all the young trees will survive more than the approximately 150 years needed before they start to develop hollows and other veteran tree characteristics.…”
Section: Important Components Of Wood-pasture Management: Forestry Prmentioning
confidence: 99%
“…They also showed, along with others, that trees with low canopies inhibit understorey growth through the competition for light, regardless of the water and nutrient relations (Blaser et al. ; Metz & Tielbörger ; Noumi et al. ).…”
Section: Introductionmentioning
confidence: 73%
“…), and some have shown that the SGH alone cannot explain the tree–grass co‐existence in savanna ecosystems (Blaser et al. ; He et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation